2013
DOI: 10.3109/0142159x.2013.765550
|View full text |Cite
|
Sign up to set email alerts
|

Integrating interprofessional education in community-based learning activities: Case study

Abstract: Faculty of Medicine/Suez Canal University (FOM/SCU) students are exposed to clinical practice in primary care settings within the community, in which they encounter patients and begin to work within interprofessional health teams. However, there is no planned curricular interaction with learners from other professions at the learning sites. As in other schools, FOM/SCU faces major challenges with the coordination of community-based education (CBE) program, which include the complexity of the design required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 9 publications
0
46
0
1
Order By: Relevance
“…Only two studies reported findings from developing countries, which were Egypt [25] and Namibia [26]. Two studies reported findings from more than one country [27], [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies reported findings from developing countries, which were Egypt [25] and Namibia [26]. Two studies reported findings from more than one country [27], [28].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [41][48] were conducted in the UK; nine studies [13], [49][56] were conducted in Canada; two in New Zealand [28], [57] and Norway [58], [59]. Among the selected studies, Australia had one study [28] and so did Singapore [60], Finland [61], Hungary [62], Egypt [25], and Namibia [26]. IPE was conducted in medical universities including teaching hospitals in 30 studies and in other health and academic institutions in eight studies.…”
Section: Resultsmentioning
confidence: 99%
“…Os relatos têm mostrado que o direcionamento dado às ações adotadas pelas IES investem em competências colaborativas, incentivam o rompimento de relações hierárquicas, a reflexão sobre a relevância do trabalho em equipe, competências relevantes no contexto da colaboração e das relações interpessoais, corroborando com experiências trazidas pela literatura 45 . Muitas instituições no mundo têm desprendido esforços no sentido de descreverem as competências centrais da educação interprofissional, que são pensadas, na maioria das vezes, em cenários da prática clínica 46,47 .…”
Section: Eip E Propet: Desvelando Potênciasunclassified
“…Students begin to encounter patients and are assigned to work with multidisciplinary health teams from their first day in medical school (Hosny et al 2013). …”
Section: Practicementioning
confidence: 99%